Pengendalian Internal pada Pondok Pesantren Al I’tishom Kubu Raya - Dewa Ruci; Dini Lestary (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
Islamic boarding school is a non-profit organization. Internal control over financial reporting in religious entities, especially Islamic boarding schools, is rarely a special concern in practice and scientific studies. In making financial reports, trust is needed to separate organizational interests and personal interests, this is to avoid conflicts of personal interest in taking advantage of the organization. The researcher wants to dig deeper into the concept of amanah, and Islamic boarding school administrators account for Islamic boarding schools' finances, not only to the people but also to know the understanding of accountability to Allah as God. Islamic boarding schools on financial management. This research method is qualitative followed by an interpretive paradigm that provides guidelines for choosing the right research methodology, namely case studies. the method of collecting and analyzing the research data is by observation, interviews, and document analysis. The results of this study are that the Al I'tishom Kubu Raya Islamic Boarding School is in accordance with the internal control structure which consists of 5 (five) components namely Control Environment, Risk Assessment, Control Activities, Information and Communication, and Supervision, at this time it has been fulfilled even though it is not overall. Likewise, the financial reports of the Al I'tishom Kubu Raya Islamic Boarding School at this time do not compile financial reports independently, but are only tasked with reporting all forms of transactions that occur at the Islamic boarding school to the financial sector. Islamic boarding school financial records are made by the assistant treasurer by keeping simple bookkeeping accompanied by proof of transactions. The existence of valid evidence and records is also a manifestation of the mandate and internal control that is applied to the Al I'tishom Kubu Raya Islamic Boarding School.